Preparation method of hydrodechlorination catalyst and application of hydrodechlorination catalyst in synthesis of chlorotrifluoroethylene
Through ultrasonic enhancement-commonly impregnated legal preparation of PD-Ni alloy catalysts, the problem of high cost and stability of the precious metal catalyst in the existing triathrine synthesis process, and realize the high selectivity and long life of catalysts.
Patent Information
- Application Number
- CN202411508731.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The existing chloroethylene synthesis process has problems such as high cost, complex process, many by-products, poor stability and short life.
Ultrasonic reinforcement-co-impregnated legal preparation PD-Ni alloy catalyst, combined with Ni as a co-catalyst and precious metal PD, reduce precious metal load, and use the synergies of additive A and additive B to regulate particle size and surface decentralization. , Improve the stability and activity of catalysts.
Effectively reduce the cost of catalysts, improve the selectivity and stability of the catalyst, extend the service life of the catalyst, and apply to industrial production.
Smart Images

Figure BDA0005104815350000131 
Figure BDA0005104815350000141 
Figure BDA0005104815350000151
Abstract
Description
Technical Field
[0001] The invention belongs to fluorine chemical technology, and specifically relates to chlorotrifluoroethylene (CTFE) synthesis technology. Background Art
[0002] Chlorotrifluoroethylene (CTFE) is one of the important monomers for the synthesis of fluorine-containing materials. Its polymerization reaction has wide application value in aviation, construction, military industry, electronic industry and other industries. The cost, purity and industrial feasibility of chlorotrifluoroethylene synthesis are the main factors affecting the development of chlorotrifluoroethylene and fluorine-containing polymer materials. Therefore, it is of great significance to develop a high-purity, low-cost and environmentally friendly chlorotrifluoroethylene preparation process.
[0003] The main methods for preparing chlorotrifluoroethylene with industrial application value are:
[0004] R113 zinc powder reduction dechlorination method: The production equipment is huge, the efficiency is low, and the production rate is difficult to control. A large amount of alcohol substances and zinc powder that are difficult to recycle are required during the reaction process, and the cost is high.
[0005] R113 catalytic hydrodechlorination method: The catalyst is mainly based on the main active components of precious metals such as Pd, Ru and Pt, and the carrier can be selected from porous materials such as activated carbon, alumina, titanium oxide, magnesium oxide, magnesium fluoride and aluminum fluoride. The reaction temperature is low and there are fewer side reactions. Although the active components of the catalyst and the reaction conditions have been continuously optimized, there is still much room for improvement in catalyst stability, cost of use, conversion rate, reaction selectivity and other aspects.
[0006] In the 1980s, Allied Corp of the United States loaded platinum metals on potassium magnesium fluoride and sodium magnesium fluoride. Hydrogen and trifluorotrichloroethane entered the reactor in the gas phase and reacted with stirring at 325-425°C. The catalyst needed to be activated in an O2 gas flow at 400-600°C to achieve a better catalytic effect.
[0007] Japanese Daikin Company's patent EP416615A1 discloses a method of using Y-type zeolite, silica, alumina, magnesia, zirconia, silicon dioxide, silicon carbide, diatomaceous earth, etc. as carriers, loading active components such as Zn, Fe, Cu, Ni, Sn, Cr or their oxides, to catalyze the hydrodechlorination of trifluorotrichloroethane to synthesize trifluorochloroethylene at 300-550°C.
[0008] Patent CN104140356A of Changshu Sanaifu Company discloses that ZnKH3 is used as a catalyst, the reaction temperature is 250-350°C, the pressure is 0.7-1.0MPa, and the residence time is 10-20s. The above catalyst can be hydrogenated and activated for repeated use. The activation temperature is 200-300°C, the activation pressure is 0.9-1.0MPa, and the residence time of the hydrogenation reaction is 5-10s.
[0009] Dalian Zhenbang Company CN1460549A discloses using coconut shell activated carbon as a carrier, loaded on a Pd-Cu-Li-La catalyst, with an average conversion rate of 81% within 800 hours, an average CTFE selectivity of 88%, and a total selectivity of CTFE and TrFE maintained at around 97%.
[0010] Sinochem Blue Sky CN112547036A discloses activated carbon as a carrier, the active component is Pd-Ir-Ni alloy, the precious metal content is low, the solid solution alloy activity is high, it is tightly combined with the carrier, has high stability and long service life.
[0011] CN113634275A of Zhejiang University of Technology discloses the use of activated carbon as a carrier, the main active component is Ru, and the auxiliary agent is at least one of B, N, and P to form an amorphous alloy with a reaction conversion rate of 90% and a selectivity of 95%. It still has a high catalytic activity after 1000 hours of reaction.
[0012] In the existing disclosed technology, although various improvements have been made in the process of synthesizing chlorotrifluoroethylene by hydrodechlorination of R113 as a raw material, there are still many problems such as high cost of precious metal catalysts, complex process, more by-products, poor stability, short life, and even the need to introduce dilution gas. Summary of the invention
[0013] In view of the defects of the prior art, the present invention provides a method for preparing a hydrodechlorination catalyst and its application in the synthesis of chlorotrifluoroethylene, which reduces the cost of precious metals, improves the sintering and agglomeration problems of precious metals in the hydrodechlorination reaction, and improves the catalytic activity of the catalyst.
[0014] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0015] First, a preparation method of a hydrodechlorination catalyst is provided, including the steps of ultrasonic enhancement-co-impregnation: an aqueous solution of Pd and Ni salts is mixed with an auxiliary metal salt, a dispersant and an impregnation liquid, and after ultrasonic enhancement for a set time, a carrier is added for impregnation, so that the impregnation liquid completely enters the pores of the carrier to achieve the effect of uniform dispersion of the metal.
[0016] Preferably, the ultrasonic enhancement time is 5-60 min, and the ultrasonic intensity is 500-1200 W; and / or, the carrier is a modified carbon carrier, and the specific surface area of the modified carbon carrier is 900-2000 m 2 / g, add the carrier and stir for 2-6h for impregnation.
[0017] Preferably, the preparation method of the modified carbon carrier is: first placing the activated carbon in a container for pretreatment to remove residual heavy metal particles, the pretreatment being at least one of acid treatment, alkali treatment and oxygen treatment; then washing with deionized water to neutrality; then ultrasonically treating the neutral activated carbon with an ultrasonic instrument; and finally drying at 80-120°C for 6-24h to obtain the modified carbon carrier.
[0018] Furthermore, the preparation method further comprises the following steps:
[0019] The impregnated solution was evaporated to dryness at 60-100°C and dried at 80-120°C in different atmospheres for 2-12h to obtain a uniformly dispersed precursor;
[0020] Calcine the dried precursor at 300-600°C in nitrogen or air for 2-12h;
[0021] The calcined precursor is reduced by a hydrogen-nitrogen mixed gas to obtain a Pd-Ni alloy catalyst.
[0022] Preferably, the Pd and Ni salts are one or more of nitrates, acetates, chlorides, oxychlorates, phosphates, isopropoxides, and citrates; and / or, the auxiliary metal salt is one of nitrates, acetates, and chlorides.
[0023] Preferably, the additive is composed of additive A and additive B, the metal element of additive A is one of Li, K, Na, Sr, Ba, Ca, Sn, and Ti; and / or the metal element of additive B is one of Fe, Co, Cu, Zn, Zr, Mn, Y, Ce, La, and Sm.
[0024] Preferably, the impregnation liquid is one of hydrochloric acid, ethanol, acetone, tetrahydrofuran and acetonitrile; and / or the dispersant is one of polyethylene glycol, sodium tripolyphosphate, sodium dodecyl sulfate and polymethylsiloxane.
[0025] Preferably, the mass fraction of Pd element in the catalyst is 0.01-2%, the mass fraction of Ni element is 0.1-10%; and / or the mass fraction of auxiliary metal element is 0.01-5%.
[0026] In addition, a method for synthesizing chlorotrifluoroethylene is also provided, which uses 1,2,2-trifluoro-1,1,2-trichloroethane and hydrogen as raw materials and adopts the catalyst.
[0027] Preferably, under mild conditions of 150°C-300°C, the ratio of H2 to raw material is 0.5-5, the reduction temperature is 200-400°C, the reduction time is 2-12h, and the total space velocity is 200-3000h -1 .
[0028] The present invention adopts the above technical solution and has the following beneficial effects:
[0029] 1. Add Ni as a co-catalyst to cooperate with the precious metal Pd. As a transition metal element, Ni has excellent ability to absorb / release electrons, which can change the electronic structure and geometric properties of the metal surface and guide the growth direction of the crystal nucleus. Compared with single metal Pd / AC, adding an appropriate amount of Ni as a co-active component reduces the loading amount of the precious metal Pd, which can not only effectively reduce the raw material cost of the catalyst, but also improve the selectivity of the catalyst for the ideal product. It has high catalytic activity and high selectivity for the main product, which is beneficial to the subsequent separation and purification process. It can also promote the formation of PdNi alloy species, with moderate activity and improved stability.
[0030] 2. The ultrasonic enhancement-co-impregnation process is used to realize the impregnation of the modified carbon carrier. The ultrasonic cavitation effect produced by ultrasonic treatment can generate shock waves and high-speed microjets with huge energy. The shock waves and high-speed microjets subject the activated carbon to strong mechanical action, which promotes the escape of residual gas in the activated carbon pores. At the same time, due to the changes in the micro-area environment, the huge pressure difference and capillary pressure prompt the impregnation liquid to carry Pd2+ and Ni2+ quickly into the activated carbon pores.
[0031] The supported Pd-Ni alloy catalyst prepared by ultrasonic enhancement-co-impregnation method has a short preparation process, low energy consumption, small particle size, uniform dispersion, high specific surface area, effectively reducing the ash content and unstable oxygen-containing group content on the surface of activated carbon, and increasing the ratio of mesoporous specific surface area to BET specific surface area, thereby improving the catalytic activity of the catalyst.
[0032] 3. The additives are composed of additive A and additive B, wherein the metal element of additive A is one of Li, K, Na, Sr, Ba, Ca, Sn, and Ti, and the metal element of additive B is one of Fe, Co, Cu, Zn, Zr, Mn, Y, Ce, La, and Sm. By adding additives, the efficient synergistic effect with the active components Pd and Ni can be enhanced, the particle size and surface dispersibility can be regulated, the reaction temperature can be lowered, and the energy consumption can be reduced. While maintaining high activity, the catalyst life can reach 2000 hours.
[0033] The specific technical solutions and beneficial effects of the present invention will be described in detail in the following specific embodiments. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The embodiment of the present invention first provides a hydrodechlorination catalyst, which is a Pd-based catalyst, which is loaded on a modified activated carbon carrier by a main catalyst and an auxiliary agent, wherein the main catalyst is Pd, and Ni is added as a co-catalyst to cooperate with the precious metal Pd. The catalyst is composed of auxiliary agent A and auxiliary agent B, wherein the metal element of auxiliary agent A is one of Li, K, Na, Sr, Ba, Ca, Sn, and Ti; and the metal element of auxiliary agent B is one of Fe, Co, Cu, Zn, Zr, Mn, Y, Ce, La, and Sm.
[0036] Furthermore, in order to prepare the above-mentioned hydrodechlorination catalyst, a method for preparing a hydrodechlorination catalyst is also provided, wherein an aqueous solution of Pd and Ni salts, a certain amount of auxiliary agent A and auxiliary agent B, and a dispersant are added, and an ultrasonic enhancement-co-impregnation method is used to impregnate the modified activated carbon carrier, and the Pd-based catalyst is obtained after drying, roasting, and reduction. Due to the use of the ultrasonic enhancement-co-impregnation method, the impregnation liquid completely enters the pores of the carrier, achieving the effect of uniform metal dispersion.
[0037] The specific preparation method is as follows:
[0038] The first step is to prepare a modified activated carbon carrier. The commercial activated carbon is placed in a three-necked flask and pretreated with dilute acid or dilute alkali for a certain period of time under constant temperature reflux to completely remove residual heavy metal particles, obtain better metal ion adsorption performance and increase the oxygen-containing functional groups on the surface of the activated carbon. Then, it is washed with deionized water while hot to neutrality, and then the neutral activated carbon sample is ultrasonically treated for 10 minutes with an ultrasonic instrument at an ultrasonic intensity of 500w to reduce the ash content in the sample and remove unstable oxygen-containing functional groups on the surface. Finally, it is dried at 80-120°C for 6-24h to obtain the modified carbon carrier.
[0039] Then, the aqueous solution of Pd and Ni salts and one or more additives are added to the impregnation solution of a certain concentration according to the mass ratio, and the salt solution is ultrasonically enhanced for a certain period of time until it is completely dissolved. Then, the activated carbon carrier to be impregnated is added and stirred at 400r / min for 2-6h.
[0040] Next, the impregnation solution was evaporated at 60-100° C. until no obvious liquid was present, and then dried at 80-120° C. under different atmospheres for 2-12 h to obtain a uniformly dispersed precursor.
[0041] The dried precursor is calcined at 300-600°C under nitrogen for 2-12 hours.
[0042] Finally, the calcined precursor is reduced by a hydrogen-nitrogen mixed gas to obtain a Pd-Ni alloy catalyst.
[0043] Based on the above technical scheme, the Pd salt, the Ni salt, and the auxiliary agent are one or more of nitrate, acetate, chloride, oxychlorate, phosphate, isopropoxide, and citrate. As a further preference, the Pd salt, the Ni salt, and the auxiliary agent are one or more of nitrate, acetate, and chloride.
[0044] Based on the above technical scheme, Pd is the main active component with a content of 0.01-2%, Ni active component content is 0.1-10%, additive A is one of Li, K, Na, Sr, Ba, Ca, Sn, Ti, additive B is one of Fe, Co, Cu, Zn, Zr, Mn, Y, Ce, La, Sm, and the total content of additives A and B is 0.01-5%. As a further preference, the Pd element content is 0.05-1.5%, the Ni element content is 0.5-6%, additive A is Sr, additive B is Sm, and the total content of additives Sr and Sm is 0.02-3%.
[0045] Based on the above technical scheme, the activated carbon carrier is one of coconut shell charcoal, wood charcoal and coal charcoal, with a specific surface area of 900-2000m 2 / g, as a further preferred embodiment, the specific surface area is 1000-1600m 2 / g.
[0046] Based on the above technical scheme, the carrier pretreatment is one or more of acid treatment, alkali treatment and oxygen treatment. As a further preference, the carrier pretreatment is acid treatment, and the type of acid can be one or more of hydrochloric acid, nitric acid and hydrofluoric acid.
[0047] Based on the above technical solution, as a further preference, the impregnation liquid is one of hydrochloric acid, ethanol and acetone.
[0048] Based on the above technical solution, as a further preference, the dispersant is one of polyethylene glycol, sodium tripolyphosphate, and sodium dodecyl sulfate.
[0049] Based on the above technical solution, as a further preferred embodiment, the ultrasonic time of ultrasonic immersion is 10-30 min, and the ultrasonic intensity is 550-950w.
[0050] In addition, it also relates to a method for synthesizing chlorotrifluoroethylene, and to the use of the above catalyst in the synthesis of chlorotrifluoroethylene. The above catalyst is used for 1,2,2-trifluoro-1,1,2-trichloroethane (HCFC-113) and hydrogen as raw materials. Under mild conditions of 150°C-300°C, the ratio of H2 to the raw material substance is 0.5-5, the reduction temperature is 200-400°C, the reduction time is 2-12h, and the total space velocity is 200-3000h. -1
[0051] As a further preference, the reaction temperature is 180-250°C, the ratio of the amount of H2 to the raw material is 0.5-3, the reduction temperature is 220-380°C, the reduction time is 2-8h, and the total space velocity is 300-1000h-1.
[0052] The above catalyst is used for the preparation of hydrodechlorination catalyst and its application in the synthesis of chlorotrifluoroethylene (CTFE), and the regeneration method is as follows:
[0053] When the catalyst conversion rate is lower than 50%, close the raw material valve, and start regeneration after calcining at 350-450℃ for 3-24h under nitrogen. First, use 1% oxygen-nitrogen mixture to calcine at 350-450℃ for 20-120h, then use 5% oxygen-nitrogen mixture to calcine for 10-48h, and then use 10% oxygen-nitrogen mixture to calcine at 350-450℃. When the gas chromatography detects no CO2 peak, stop calcining. Then cool down to 200℃ and keep for 2-48h, slowly heat up to 300℃, and gradually introduce hydrogen and nitrogen mixture for reduction. Then cool down to the reaction temperature and wait for the reaction to start.
[0054] Compared with the prior art, the present invention has the following technical effects:
[0055] 1. The transition metal element Ni has an excellent ability to absorb / release electrons, which can change the electronic structure and geometric properties of the metal surface and guide the growth direction of the crystal nucleus. Compared with single metal Pd / AC, adding an appropriate amount of Ni as a co-active component reduces the loading amount of the precious metal Pd, which can not only effectively reduce the raw material cost of the catalyst, improve the selectivity of the catalyst for the ideal product, and facilitate the subsequent separation and purification process, but also promote the formation of PdNi alloy species with moderate activity and improved stability.
[0056] 2. The ultrasonic cavitation effect produced by ultrasonic treatment can generate huge energy shock waves and high-speed microjets. The shock waves and high-speed microjets subject the activated carbon to strong mechanical action, which promotes the escape of residual gas in the activated carbon pores. At the same time, due to the change of micro-area environment, the huge pressure difference and capillary pressure cause the impregnation liquid to carry Pd 2+ and Ni 2+Rapidly penetrate into the activated carbon pores. The supported Pd-Ni alloy catalyst prepared by ultrasonic enhancement-co-impregnation method has a short preparation process and low energy consumption, effectively reducing the ash content and unstable oxygen-containing groups on the surface of activated carbon, and increasing the ratio of mesopore specific surface area to BET specific surface area, thereby improving the catalytic activity of the catalyst.
[0057] 3. By adding additives Sr and Sm, the efficient synergistic effect with the active components Pd and Ni is enhanced, the particle size and surface dispersibility are regulated, the reaction temperature is lowered, and the energy consumption is reduced. While maintaining high activity, the catalyst life can reach 2000 hours.
[0058] The technical solution of the present invention is described below in conjunction with specific examples.
[0059] Comparative Example 1: Preparation of Pd / AC-1 Catalyst
[0060] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 15% HNO3 solution, reflux at a constant temperature of 50℃ for 2h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, the ultrasonic intensity is 500w, and finally dry it at 80℃ for 24h to obtain the modified carbon carrier. Weigh 0.555g PdCl2 and 0.2g polyethylene glycol and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, continue stirring in a water bath for 2h, heat at 100℃ and evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor is calcined at 300℃ in a nitrogen atmosphere for 2h, and the calcined precursor is reduced by a hydrogen-nitrogen mixed gas to obtain a Pd / AC-1 catalyst.
[0061] Example 1: Preparation of Pd / AC catalyst
[0062] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 15% HNO3 solution, reflux at a constant temperature of 50℃ for 2h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 80℃ for 24h to obtain the modified carbon carrier. Weigh 0.555g PdCl2 and 0.2g polyethylene glycol and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 10min, with an ultrasonic intensity of 550w, then transfer it to a water bath and continue stirring for 2h, heat at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300° C. in a nitrogen atmosphere for 2 h, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd / AC catalyst.
[0063] Example 2: Preparation of Pd-Ni / AC catalyst
[0064] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 5% HNO3 solution, reflux at a constant temperature of 50℃ for 2h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 80℃ for 24h to obtain the modified carbon carrier. Weigh 0.555g PdCl2, 2.146g NiCl2 and 0.2g polyethylene glycol and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 10min, with an ultrasonic intensity of 550w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300° C. in a nitrogen atmosphere for 2 h, and then the calcined precursor was reduced with a hydrogen-nitrogen mixed gas to obtain a Pd-Ni / AC catalyst.
[0065] Example 3: Preparation of Pd-Ni-Sr / AC catalyst
[0066] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 5% HNO3 solution, reflux at a constant temperature of 50℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 80℃ for 24h to obtain the modified carbon carrier. Weigh 0.555g PdCl2, 2.146g NiCl2, 0.346g SrCl2 and 0.2g sodium tripolyphosphate and add them together to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 10min, with an ultrasonic intensity of 550w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-Sr / AC catalyst.
[0067] Example 4: Preparation of Pd-Ni-K / AC catalyst
[0068] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 5% HCl solution, reflux at a constant temperature of 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.555g PdCl2, 2.146g NiCl2, 0.867g KCl and 0.2g sodium tripolyphosphate and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 10min, with an ultrasonic intensity of 550w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-K / AC catalyst.
[0069] Comparative Example 2: Preparation of Pd-Ni-Sm / AC-1 Catalyst
[0070] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 5% HCl solution, reflux at a constant temperature of 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.346gPdCl2, 2.146gNiCl2, 0.463gSmCl3 and 0.2g sodium tripolyphosphate and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 30min, with an ultrasonic intensity of 720w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300°C in an air atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-Sm / AC-1 catalyst.
[0071] Example 5: Preparation of Pd-Ni-Sm / AC catalyst
[0072] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 5% HCl solution, reflux at a constant temperature of 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.346gPdCl2, 2.146gNiCl2, 0.463gSmCl3 and 0.2g sodium tripolyphosphate and add them to the prepared 30ml ethanol solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 30min, with an ultrasonic intensity of 720w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 12h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-Sm / AC catalyst.
[0073] Example 6: Preparation of Pd-Ni-Sr-Sm / AC catalyst
[0074] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 20% HF solution, reflux at a constant temperature of 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min with an ultrasonic intensity of 500w, and finally dry at 110℃ for 24h to obtain the modified carrier. Weigh 0.346g PdCl2, 2.146g NiCl2, 0.429g Sr(NO3)2, 0.863g Sm(NO3)3 and 0.2g polyethylene glycol and add them to the prepared 30ml acetone solution. Stir at 400r / min for 10min, then add 15g modified carrier, then ultrasonicate the sample for 30min with an ultrasonic instrument, the ultrasonic intensity is 720w, then transfer to a water bath and continue stirring for 2h, heat to 100℃ and evaporate until there is no obvious liquid, and dry in an oven at 120℃ for 6h to obtain a uniformly dispersed precursor. Finally, the dried precursor is calcined at 300℃ in a nitrogen atmosphere for 4h, and then the calcined precursor is reduced by a hydrogen-nitrogen mixed gas to obtain a Pd-Ni-Sr-Sm / AC catalyst.
[0075] Example 7: Preparation of Pd-Ni-K-Mn / AC Catalyst
[0076] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 20% HF solution, reflux at a constant temperature of 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.346gPdCl2, 2.146gNiCl2, 0.169gKNO3, 0.628gMn(NO3)3 and 0.2gpolyethylene glycol and add them to the prepared 30ml acetone solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 30min, with an ultrasonic intensity of 900w, then transfer it to a water bath and continue stirring for 2h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 120℃ for 6h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 300°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-K-Mn / AC catalyst.
[0077] Example 8: Preparation of Pd-Ni-Ca-Y / AC Catalyst
[0078] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 10% HCl solution, reflux at 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.346gPdCl2, 2.146gNiCl2, 0.429gCa(NO3)2, 0.492gYCl3 and 0.2g polyethylene glycol and add them to the prepared 30ml HCl solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 30min, with an ultrasonic intensity of 900w, then transfer it to a water bath and continue stirring for 3h, heat to 80℃ and evaporate to dryness until there is no obvious liquid, and dry it in an oven at 100℃ for 4h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 380°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced with a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-Ca-Y / AC catalyst.
[0079] Example 9: Preparation of Pd-Ni-Ba-Ce / AC catalyst
[0080] Weigh 30g of commercial coconut shell charcoal and place it in a three-necked flask, add 300mL of 10% HCl solution, reflux at 80℃ for 4h, then wash with deionized water while hot until neutral, then use an ultrasonic instrument to ultrasonicate the neutral activated carbon sample for 10min, with an ultrasonic intensity of 500w, and finally dry it at 110℃ for 24h to obtain the modified carrier. Weigh 0.346gPdCl2, 2.146gNiCl2, 0.562gBaCl2, 0.859gCe(NO3)3 and 0.2gpolyethylene glycol and add them to the prepared 30ml HCl solution, stir at 400r / min for 10min, then add 15g of the modified carrier, then use an ultrasonic instrument to ultrasonicate the sample for 30min, with an ultrasonic intensity of 900w, then transfer it to a water bath and continue stirring for 3h, heat it at 100℃ to evaporate until there is no obvious liquid, and dry it in an oven at 100℃ for 4h to obtain a uniformly dispersed precursor. Finally, the dried precursor was calcined at 350°C in a nitrogen atmosphere for 4 hours, and then the calcined precursor was reduced by a hydrogen and nitrogen mixed gas to obtain a Pd-Ni-Ba-Ce / AC catalyst.
[0081] Example 10: Catalyst application experiment
[0082] 10 g of the catalyst prepared in Examples 1-9 were respectively loaded into a nickel tube fixed bed tubular reactor with an inner diameter of 12 mm, and then reduced at a temperature of 380°C for a reduction time of 2 h, lowered to the desired reaction temperature, and the raw materials were introduced with a molar ratio of H2 to the raw material of 3. The tail gas was washed with water and KOH solution, dried, and analyzed by gas chromatography. The chromatographic column used was Agilent DB-624, carrier gas: nitrogen, injection port 100°C, column box temperature 50°C, and FID detector 220°C.
[0083] Calculation method of reaction instantaneous conversion rate and selectivity:
[0084] The product composition was analyzed by gas chromatography, and the molar number of each product in the product was calculated by external standard method.
[0085]
[0086] Table 1 Catalyst application test results
[0087]
[0088] From the experimental results of different catalysts in Table 1, the selectivity of Pd / AC catalyst prepared by simple impregnation method for chlorotrifluoroethylene is very low, and the selectivity is greatly improved by the method of ultrasonic enhancement-co-impregnation. On the basis of this method, adding Ni metal as a co-active component can effectively improve the selectivity and activity of chlorotrifluoroethylene, and adding an appropriate amount of alkaline earth metal Sr and rare earth metal Sm can effectively increase the reaction temperature and reduce energy consumption.
[0089] Example 11 Catalyst stability test
[0090] 20 g of the catalyst prepared in Comparative Example 1, Example 2 and Example 6 were respectively loaded into a nickel tube fixed bed tubular reactor with an inner diameter of 12 mm, and then reduced to 350°C for 4 h, and then lowered to the desired reaction temperature of 180°C. The raw materials were introduced with a molar ratio of H2 to the raw material of 3. The tail gas was washed with water and KOH solution and dried, and analyzed by gas chromatography. The chromatographic column used was Agilent DB-624, carrier gas: nitrogen, injection port 100°C, column box temperature 50°C, and FID detector 220°C.
[0091] Table 2 Catalyst stability test results
[0092]
[0093] From the stability test results of the three catalysts in Table 2, the activated carbon-supported Pd-Ni multimetallic catalyst prepared by the ultrasonic enhancement-co-impregnation method enhances the strong interaction between Pd and Ni and the activated carbon, and inhibits the agglomeration of precious metals. The addition of additives produces a synergistic effect with the active component Pd-Ni, improves the reducibility of the catalyst, and improves the selectivity and stability of the catalyst, making it suitable for industrial production.
[0094] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for preparing a hydrodechlorination catalyst, characterized in that: The method comprises the steps of ultrasonic strengthening and co-impregnation: mixing an aqueous solution of Pd and Ni salts with an auxiliary metal salt, a dispersant and an impregnation solution, and adding the solution to a carrier for impregnation after ultrasonic strengthening for a set time, so that the impregnation solution completely enters the pores of the carrier to achieve a uniform dispersion of the metal.
2. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The ultrasonic enhancement time is 5-60 min, and the ultrasonic intensity is 500-1200w; and / or, the carrier is a modified carbon carrier, and the specific surface area of the modified carbon carrier is 900-2000m 2 / g, add the carrier and stir for 2-6h for impregnation.
3. A method for preparing a hydrodechlorination catalyst according to claim 2, characterized in that: The preparation method of the modified carbon carrier is as follows: firstly, the activated carbon is placed in a container for pretreatment to remove residual heavy metal particles, wherein the pretreatment is at least one of acid treatment, alkali treatment and oxygen treatment; then, it is washed with deionized water until it is neutral; then, the neutral activated carbon is ultrasonically treated with an ultrasonic instrument; and finally, it is dried at 80-120° C. for 6-24 hours to obtain the modified carbon carrier.
4. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The preparation method further comprises the following steps: The impregnated solution was evaporated to dryness at 60-100°C and dried at 80-120°C in different atmospheres for 2-12h to obtain a uniformly dispersed precursor; Calcine the dried precursor at 300-600°C in nitrogen or air for 2-12h; The calcined precursor is reduced by a hydrogen-nitrogen mixed gas to obtain a Pd-Ni alloy catalyst.
5. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The Pd and Ni salts are one or more of nitrates, acetates, chlorides, oxychlorates, phosphates, isopropoxides, and citrates; and / or the auxiliary metal salt is one of nitrates, acetates, and chlorides.
6. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The additive is composed of additive A and additive B, wherein the metal element of additive A is one of Li, K, Na, Sr, Ba, Ca, Sn, and Ti; and / or the metal element of additive B is one of Fe, Co, Cu, Zn, Zr, Mn, Y, Ce, La, and Sm.
7. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The impregnation liquid is one of hydrochloric acid, ethanol, acetone, tetrahydrofuran and acetonitrile; and / or the dispersant is one of polyethylene glycol, sodium tripolyphosphate, sodium dodecyl sulfate and polymethylsiloxane.
8. The method for preparing a hydrodechlorination catalyst according to claim 1, characterized in that: The mass fraction of Pd element in the catalyst is 0.01-2%, the mass fraction of Ni element is 0.1-10%; and / or the mass fraction of auxiliary metal element is 0.01-5%.
9. A method for synthesizing chlorotrifluoroethylene, characterized in that: 1,2,2-trifluoro-1,1,2-trichloroethane and hydrogen are used as raw materials, and the catalyst described in any one of claims 1 to 8 is used.
10. A method for synthesizing chlorotrifluoroethylene according to claim 9, characterized in that: Under mild conditions of 150℃-300℃, the ratio of H2 to raw material is 0.5-5, the reduction temperature is 200-400℃, the reduction time is 2-12h, and the total space velocity is 200-3000h -1 .
Citation Information
Patent Citations
Novel preparation method for green CTFE
CN104140356A
Trifluorotrichloroethane hydrodechlorination catalyst and preparation method thereof
CN112547036A
Catalyst for catalytic hydrodechlorination and preparation method and application thereof
CN113634275A
Catalyst for preparing trifluorochloroethylene and trifluoroethylene by using CFC-113 catalytic hydro-dechlorination and its preparation method
CN1460549A
Cited By
Trifluorochloroethylene continuously prepared based on microchannel reactor and preparation method thereof
CN121537246A
Method for hydrodechlorination of chloroaromatic compounds
RU2855611C1